Risk Factors Associated with Childhood Diarrhoae in an Urban Field Practice Area: A Community-Based Cross-Sectional Analytical Study - Morale Bhagwan; Dixit Jagannath (Universitas Airlangga, 2026)
Childhood diarrhoea remains a leading cause of morbidity among under-five children, particularly in the densely populated informal settlements of low- and middle-income countries, where water, sanitation and hygiene (WASH) conditions are often inadequate. Recent community-based evidence from urban field practice areas in western India is limited. This study estimated the prevalence of diarrhoea and its associated risk factors among under-five children in an urban field practice area attached to a medical college. A community-based cross-sectional analytical study was conducted among 621 children under five years of age, selected by simple random sampling from a line list of children registered across 14 Anganwadi centres. Diarrhoea was defined as the passage of three or more loose stools within 24 hours during the two weeks preceding the survey. Socioeconomic status was assessed using the Modified Kuppuswamy classification (2023). Data were collected through house-to-house interviews using a pre-tested, validated semi-structured questionnaire. Chi-square tests and multivariable logistic regression were applied; adjusted odds ratios (AOR) with 95% confidence intervals (CI) were calculated. The prevalence of diarrhoea was 10.47% (n=65). On multivariable analysis, unimproved drinking water (AOR 4.29; 95% CI 2.15–8.57), lack of handwashing before feeding (AOR 3.14; 95% CI 1.70–5.78), unimproved sanitation (AOR 3.07; 95% CI 1.42–6.65) and single-room occupancy (AOR 1.87; 95% CI 1.04–3.35) emerged as independent risk factors. Childhood diarrhoea remains an important public health concern in this urban setting. Improving sanitation, ensuring access to safe drinking water and promoting hand hygiene may substantially reduce diarrhoeal morbidity among children under five.